THE INFLUENCE OF PURCHASE EXPERIENCE, TRUST AND PRICE TOWARD CUSTOMERS PURCHASE DECISION ON TOKOPEDIA - Ircha Mahendra Sakti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This research aimed to determine the effect of the purchase experience, trust and price on purchase decisions on one of the online shopping sites in Indonesia, Tokopedia. This correlational/associative research was conducted to determine the effect of one or more independent variables on the dependent variable. This research used a sample of 200 respondents, namely students of Universitas Brawijaya Malang by using a questionnaire conducted online. The data was analyzed by multiple linear regression analysis and hypothesis testing using t-test, which was processed by SPSS software ver. 21. The results of the research noted that the purchase experience, trust and price variables have a positive and significant influence on consumer purchase decisions in Tokopedia. The need to improve the shopping experience through a good customer experience, increase consumer confidence by providing a good shopping process, and maintain and improve the quality of price by setting a reasonable price. If Tokopedia is able to fulfill it, then experience, trust, and price will have a positive influence on Tokopedia purchase decision.Keywords: Purchase Experience, Trust, Price, Purchase Decision